Characteristic Architectural Elements of Traditional Barbaros Houses with a Single-Living Space and Their Relationship with Daily Life - Şeyma Sarıbekiroğlu; Fatma Nurşen Kul (Art-Sanat)
Barbaros is a rural settlement in Urla, İzmir, Turkey. This study aims to understand the architectural elements of Barbaros houses with a single-living space, their spatial organization, relation with daily life, and the local terminology for them. Moreover, it is aimed to reveal possible similarities and dissimilarities between architectural elements of other singleliving space rural houses in different settlements in close geography. The site survey data was collected in 2016, 2017, and 2020. Fourteen houses were examined, all of which still preserve their original spatial characteristics and architectural elements. The plans and architectural elements of each of the 14 buildings were documented in sketches and photographs. The architectural elements of each house and their characteristics, including form, material, and location in space, were analyzed. The Barbaros case was compared with other rural settlements in Çeşme, Karaburun and Urla. Oral interviews were conducted with 13 people to reveal the relationship between architectural elements and daily life.